2011
DOI: 10.1007/s11120-011-9644-2
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation of the resurrection plant Haberlea rhodopensis at high temperature

Abstract: Haberlea rhodopensis plants, growing under low irradiance in their natural habitat, were desiccated to air-dry state at a similar light intensity (about 30 μmol m(-2) s(-1)) under optimal (23/20°C, day/night) or high (38/30°C) temperature. Dehydration of plants at high temperature increased the rate of water loss threefold and had a more detrimental effect than either drought or high temperature alone. Water deficit decreased the photochemical activity of PSII and PSI and the rate of photosynthetic oxygen evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The photosynthetic apparatus associated with PSII is highly sensitive to heat, drought, and various other stresses [13], [28] that usually reduce the photosynthetic rate and increase the rate of photorespiration [9], [29]. In the present study, a continuous reduction in photosynthetic rate, which reflected the level of stress, was deduced from the change in chlorophyll fluorescence ( F v / F m ) under three different stress regimes (Figure 2A and B).…”
Section: Discussionmentioning
confidence: 55%
“…The photosynthetic apparatus associated with PSII is highly sensitive to heat, drought, and various other stresses [13], [28] that usually reduce the photosynthetic rate and increase the rate of photorespiration [9], [29]. In the present study, a continuous reduction in photosynthetic rate, which reflected the level of stress, was deduced from the change in chlorophyll fluorescence ( F v / F m ) under three different stress regimes (Figure 2A and B).…”
Section: Discussionmentioning
confidence: 55%
“…In addition, the RWC of R. nathaliae decreased from 94.5 % to 3.6 % during dehydration (Jovanoviç et al 2011). Kinetics of relative water content during dehydration-rehydration cycle was reported from other authors in R. serbica (Augusti et al 2001;Quartacci et al 2002;Veljovic-Jovanoviç et al 2006;Sgherri et al 2004) and Haberlea rhodopensis (Nagy- Deri et al 2011;Mihailova et al 2011;Djilianov et al 2011;Georgieva et al 2010).…”
Section: Relative Water Contentmentioning
confidence: 51%
“…The results generally concluded that PSII was liable to be injured by high temperature, and PSII components including oxygen-evolving complex, reaction center, light-harvesting complex and electron acceptor had different heat sensitivity. Both slight change and obvious decline in PSI activity were reported in plants exposed to high temperature, and consistently, PSI was demonstrated to be more tolerant than PSII (Sayed et al, 1989;Boucher and Carpentier, 1993;Mihailova et al, 2011;Essemine et al, 2012). However, PSI and PSII performances were not simultaneously monitored in these studies.…”
Section: Introductionmentioning
confidence: 90%